KONSEP TERAPI SUGESTI UNTUK ANAK USIA DINI MENURUT A. HAMAM ROSIDI - Muslimin; Diah Nur Hidayati (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
In the book Parenting Suggestion by A. Hamam Rosidi, S.Pd, MA, he clearly explains how we can solve children's problems using suggestion therapy, and reveals the secrets of effective suggestion in educating children. Based on the background of the problem, this research is expected to provide answers to the formulation of the problem (1) What is the concept of suggestion therapy in early childhood? (2) How is the concept of suggestion therapy for early childhood according to A. Hamam Rosidi in the Parenting Suggestion book? Based on the formulation of the problem, this study aims (1) to find out the concept of suggestion therapy in early childhood (2) to find out the concept of suggestion therapy for early childhood according to A. Hamam Rosidi in the Parenting suggestion book. This research uses library research and character study approach through qualitative research methods. The results of this study led to the conclusion that the concept of suggestion therapy in early childhood is to find out the child's problems, perform hypnosis by penetrating the critical factor, give suggestions and bring the child out of the hypnotic state. While the concept of suggestion therapy in early childhood according to A. Hamam Rosidi is to build closeness with children and know the secrets and effective time to give suggestions to children.